URGENSI PENDIDIKAN AGAMA ISLAM TERHADAP STUDENT WELL-BEING DALAM MENANGGULANGI KRISIS MORAL DI PESANTREN - Alfina Pasca Khaira (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
The urgency of Islamic Education on student well-being in overcoming moral decline in pesantren today must be immediately corrected and get serious attention from educators and parents. This study aims to provide an understanding that the right solution in overcoming the moral crisis in pesantren is to pay attention to the formation of student well-being through Islamic education. This research is qualitative, and the data collection process was carried out in two stages, namely primary data collection by interviewing three teachers from different pesantren, and the second stage of secondary data collection from related books and journals. Data analysis techniques have four steps: data collection, data processing (data reduction), grouping core data according to research needs, presenting data in narrative form, and drawing conclusions. The result of the research is that the cultivation of strong religious (Islamic) education both in the family (parents) and at school (teachers) can form good student well-being so that children do not easy to commit moral deviations wherever they are and maintain pesantren as the most effective Islamic educational institution in transmitting and transferring religious knowledge.